PROSEDUR AUDIT ATAS AKUN PIUTANG USAHA PADA PT BP OLEH KAP KANAKA PURADIREDJA, SUHARTONO (NEXIA INTERNASIONAL) - Lutfia Minati (2023)
The financial statements describe the results of the company's performance during one reporting year. The main objective of financial reports is to provide sufficient and accurate information to users of financial reports so that they can be used as a basis for making decisions. Trade receivables are amounts of money that must be received by a company as a result of selling goods or services to customers who have not been paid. An audit of receivables has the objective of assessing receivable balances and determining whether receivables are presented accurately and in accordance with existing accounting principles. Audit procedures are procedures carried out by the auditor to test the financial statements presented to the company's management. The accounts receivable audit procedure is a series of activities carried out by KAP KPS for PT BP which is engaged in the plantation sector and has been carried out in a structured manner in accordance with issued standards.